Współczesne formy uczestnictwa religijnego: pomiędzy indywidualizacją a społeczną mobilizacją. Fenomen zróżnicowania w optyce empirii i dyskursie medialnym - Szymczak, Wioletta; Szulich-Kałuża, Justyna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2025)
The subject of analysis in this article is the declarations of participation in select religious events available in the Catholic Church in Poland. It will be an exploratory search on the similarities and differences among respondents, those who participate in these events, with an analysis of media discourses on the topic of events that are distinguished from others according to the above criteria. The considerations are based on the complementary use of quantitative methods (nationwide representative survey, cluster analysis) and qualitative methods (discourse analysis using the framing technique). The first part of the paper identifies three of the ten religious events in our research, and the participants formed a most homogenous internal group that was different from the rest. The next part situates the analysis in the context of media processes. Its goal is to determine what knowledge about the select events make up the media discourse, the linguistic and visual framework this is placed in and the meaning-creating role of these discourses while indicating the centres and fringes of frameworks. The conclusions formulated and based on the analyses note the titular phenomenon of diversification of forms of religious participation, saturating it substantively by recognising and categorising the content aspects of this differentiation.